Microwave dielectric properties of a low firing and temperature stable lithium magnesium tungstate (Li4MgWO6) ceramic with a rock-salt variant structure. Issue 16 (December 2021) - Zhang, Xing; Fang, Zixuan; Jiang, Yinghao; Wang, Mingxia; Gee, Stephen; Zhou, Lei; Yang, Hongyu; Si, Feng; Zhao, Peng; Xiong, Zhe; Zhang, Shuren; Tang, Bin
Abstract: The Li4 MgWO6 ceramic was synthesized by the conventional solid-state reaction method, and its sintering behavior and microwave dielectric properties were studied for the first time. The XRD patterns and structural refinements indicated that Li4 MgWO6 formed an orthorhombic phase at temperatures above 900 °C, and TEM analyses confirmed the ordered and layered rock-salt superstructures for the orthorhombic Li4 MgWO6 . The SEM photographs and relative density curve showed that the sample sintered at 950 °C had the highest densification. When sintered at 950 °C in a WO3 -rich atmosphere for 4 h, Li4 MgWO6 had the following optimum properties: εr = 15.06±0.33, Q × f = 28, 300±600 GHz ( f = 10.1 GHz), and τ f = 0.9±3.4 ppm/°C. Compared with other reported low permittivity compounds, Li4 MgWO6 shows more potential for the Low-Temperature Cofired Ceramics (LTCC) substrate materials due to its intrinsic low sintering temperature, novel temperature stability, and relatively low dielectric loss.